The radiation from ultrafast point dipoles, moving uniformly near chiral media - V. N. Kadantsev (Российский технологический журнал)
The article discusses the features of the radiation of ultrafast point clusters of charged particles moving uniformly near a gyrotropic medium interface. It is shown that some types of electromagnetic radiation – transient and/or Cherenkov radiation – have the characteristics of superchiral fields. Therefore, they can be effectively used to study chiral structures (for example, to detect circular dichroism, the frequency characteristics of refractive indices), various materials, including biomaterials. Ultrafast (relativistic) particles can serve as a «tool» not only for studying the structure of various materials. They can also be used as «generators» of quasiparticles that determine the «dynamic» properties of the materials under study, as well as the features of their interaction with radiation of various nature and response to external influences. In this paper, some types of circularly polarized EM waves propagating in optically active (magnetoactive, naturally active, gyrotropic, and chiral) media are considered. Using the generalized reciprocity theorem for media characterized by the Hermitian permittivity tensor, we consider the transient and Cherenkov radiation excited by a uniformly moving bunch of charged particles when it crosses (or moves along) the interface of media, one of which is an optically active gyrotropic medium. It is shown that the superchiral electromagnetic fields of the transition and Cherenkov radiation of dipoles can serve as a source of chiral collective excitations in magnetoactive and naturally active media. The investigated mechanisms of interaction of electromagnetic radiation with chiral materials (structures and media) are one of the possible physical approaches to solving the problem of the chiral purity of the biosphere and to elucidate the factor of deracemization of the organic primeval environment. A new hypothesis is presented, suggesting that ultra-high-speed clumps of charged particles of cosmic origin can cause deracemization of the prebiosphere.